Grazing systems effects on infiltration rates and sediment production of a bushed glassland Buchuma, Kenya. - Mbakaya, D.S. (Texas A&M University, 1985)
A drip-type rainfall simulator was used to assess effects of grazing systems and vegetation on infiltration rates and sediment production at Buchuma Range Research Station, Kenya. Four livestock grazing treatments were studied: High Intensity Low Frequency, rotation, moderate continuous and non-grazing. A combination of cattle and goats were utilized in each treatment. Two vegetation types and bare ground were also studied: Chloris roxbughiana, Grewia bicolor and bare ground (unvegetated). The study objectives were to determine 1. the influences of High Intensity Low Frequency (HILF), Rotation Grazing (RG), Moderate Continuous Grazing (MCG) and livestock exclosure(EXC) on infiltration rates and sediment production, 2. the influence of Grewia bicolor, Chloris roxburghiane and bare ground on infiltration rates and sediment production, 4. interrelationships of plant standing crop and cover, soil bulk density, organic matter, soil moisture content, texture, aggregate stability and micro relief with infiltration rates and sediment production. Infiltration rates were consistently greater in vegetated plots than unvegetated plots. However, in the vegetated plots there was significant difference between the two vegetation types. Infiltration rates were greater under Grewia bicolor than in Chloris roxburghiana. Sediment production was greater from unvegetated plots than from vegetated plots. The EXC had the greatest infiltration rate, although it was not significantly different from High Intensity Low Frequency before grazing (HILFI), Rotation Grazing before grazing (RG1) and Rotation Grazing after grazing (RG2). The MCG pasture infiltration rates were less than other pastures although they were not significantly greater than RG pastures. During August the greatest sediment production occurred from MCG pastures although it was not significantly greater than RG pastures. During December greatest sediment production was from RG2 pastures although it was only significantly greater than the EXC. Stepwise multiple regression identified variables associated with vegetation: foliar cover, litter cover, standing crop and litter accumulation and soil aggregate stability as being the most important in influencing infiltration rates and sediment production.